2013
DOI: 10.1186/1744-8069-9-24
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 Sensitizes TRPV1 through Cdk5 Signaling in Odontoblast-Like Cells

Abstract: BackgroundOdontoblasts are specialized cells that form dentin and they are believed to be sensors for tooth pain. Transforming growth factor-β1 (TGF-β1), a pro-inflammatory cytokine expressed early in odontoblasts, plays an important role in the immune response during tooth inflammation and infection. TGF-β1 is also known to participate in pain signaling by regulating cyclin-dependent kinase 5 (Cdk5) in nociceptive neurons of the trigeminal and dorsal root ganglia. However, the precise role of TGF-β1 in tooth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…signaling sensitizes TRPV1 in primary sensory neurons. [14][15][16] ] i increase. Thus, another possibility mediating the acute effects of TGF-β1 is that calcium released from intracellular calcium pools as a second message opens one or more non-selective cation channels in direct or indirect ways, thus resulting in robust depolarization and discharges.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…signaling sensitizes TRPV1 in primary sensory neurons. [14][15][16] ] i increase. Thus, another possibility mediating the acute effects of TGF-β1 is that calcium released from intracellular calcium pools as a second message opens one or more non-selective cation channels in direct or indirect ways, thus resulting in robust depolarization and discharges.…”
Section: Discussionmentioning
confidence: 96%
“…[8][9][10] However, the role of TGF-β1 in pain processing is controversial. Evidence suggests that TGF-β1 has protective effects against neuropathic pain in the central nervous system, 11,12 while in peripheral nervous system, TGF-β1 is recently reported as an algogenic substance that contributes to peripheral sensitization by downregulation of the KCNA4 gene, 13 or activation of cyclin-dependent kinase-transient receptor potential vanilloid type 1 (Cdk5-TRPV1) signaling 14,15 and transforming growth factor β activated kinase 1 (TAK1)/protein kinase C (PKC)-TRPV1 signaling. 16 As mentioned in those studies, [13][14][15][16] TGF-β1 is a complex modulator of sensory neuronal function, and its signaling pathway in the induction and development of pancreatic pain in rats with chronic pancreatitis was not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…We reported earlier that Cdk5 regulates pain signaling in nociceptive neurons of the dorsal root ganglion (DRG) and trigeminal ganglion (TG) [41; 46; 47; 52]. Cdk5 activity increases during peripheral inflammation, by the action of cytokines such as TNF-α [47; 53; 57] and TGF-β1 [54; 56]. Moreover, we found that Cdk5 phosphorylates the transient receptor potential vanilloid 1 (TRPV1) in Thr407, a key ion channel implicated in pain, increasing its function [25; 33; 40; 47; 54; 56].…”
Section: Introductionmentioning
confidence: 99%
“…Cdk5 activity increases during peripheral inflammation, by the action of cytokines such as TNF-α [47; 53; 57] and TGF-β1 [54; 56]. Moreover, we found that Cdk5 phosphorylates the transient receptor potential vanilloid 1 (TRPV1) in Thr407, a key ion channel implicated in pain, increasing its function [25; 33; 40; 47; 54; 56]. Remarkably, TRPV1 is phosphorylated in Ser116 and Thr370 by PKA [35], and its dephosphorylation is important for the desensitization process [36].…”
Section: Introductionmentioning
confidence: 99%
“…Cdk5 activity is largely dependent on the availability of its activators, p35 and p39 (8,(15)(16)(17). Transcription of p35 is under the control of early growth response protein 1 (EGR-1) (18)(19)(20). p35 is degraded by two main pathways: the ubiquitin-proteasome pathway is the predominant form of degradation in fetal neurons, whereas, in adult neurons, p35 is preferentially cleaved to p25 by the calciumdependent protease calpain (21-23).…”
mentioning
confidence: 99%